Chapitre VI. L’hybridité générique - Lorre-Johnston, Christine (Presses Sorbonne Nouvelle, 2018)
Vollmann refers to The Rifles as a book that “straddles the gap between fiction and documentary history” (409). The novel’s narrator is difficult to pin down, because of his polymorphous omnipresence and multiple narrative voices. This precludes any attempt to distinguish, within the narration, between fiction and anthropological, historical or travel discourse. This chapter, in conclusion to the other chapters of the book, aims to investigate the generic hybridization of The Rifles and the process of fragmentation of language and genres.The chapter builds on louri Lotman’s idea that in a literary text, by shifting from one system of expression to another, one genre to another, the writer creates “noise” that, paradoxically, is a constant source of information. This strategy plays on the relation between writer and reader, whose reading contract, in The Rifles, is blurred from the beginning and whose expectations are therefore unsettled. The chapter reads The Rifles together with three other texts, in order to examine Vollmann’s way of dealing with dislocation and displacement by employing generic displacement and transformation. Les derniers rois de Thulé (1955, 1989), by Jean Malaurie, is an anthropological narrative about his work with Greenland Inuit; Passage to Juneau (1999), the travel narrative in which Jonathan Raban retraces George Vancouver’s search for the Inside Passage in 1791; and A Discovery of Stangers (1994), a historical novel in which Rudy Wiebe retells John Frankin’s 1820-21 land expedition to the Polar Sea.The conclusion to the anthropological enquiry carried out in Les derniers rois de Thulé consists in denouncing and rejecting the destruction of the Inuit people. The Rifles adopts a similar stance, but conveys it by framing the narrative with testimonies, and by moving away from this form to fiction in the bulk of the text. Further, illustrations have a documentary function in Thulé, whereas they aim at subjective representation in The Rifles. Overall, while Malaurie in Thulé familiarizes ...